2017
DOI: 10.1007/s11999-016-5010-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Surgeon Experience Impact the Risk of Complications After Bernese Periacetabular Osteotomy?

Abstract: Background Bernese periacetabular osteotomy (PAO) is a technically challenging procedure with potential risk for major complications and a previously reported steep learning curve. However, the impact of contemporary hip preservation fellowships on the learning curve of PAO has not been established. Questions/purposes (1) What was the frequency of major complications during the PAO learning curve of two surgeons who recently graduated from hip preservation fellowships? (2) Is increasing level of experience ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 29 publications
2
30
0
2
Order By: Relevance
“…Of the PAOs performed during the learning phase of the mentorship program (first 26 PAOs), none had a Sink Grade III or IV complication at 12 months. Similar to Novais et al [34], our study suggests that the risk of a Grade III or IV complication did not decrease with increasing surgeon experience. The reoperation rate beyond the 12-month postoperative period was not dissimilar to many other published series [11,49].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Of the PAOs performed during the learning phase of the mentorship program (first 26 PAOs), none had a Sink Grade III or IV complication at 12 months. Similar to Novais et al [34], our study suggests that the risk of a Grade III or IV complication did not decrease with increasing surgeon experience. The reoperation rate beyond the 12-month postoperative period was not dissimilar to many other published series [11,49].…”
Section: Discussionsupporting
confidence: 90%
“…The best method of training a surgeon to perform this complex procedure is yet to be determined. Although distant mentorship may be a potential method of learning PAO, Novais et al [34] have shown that two young surgeons initially trained within a formal structured hip preservation fellowship can perform PAO with a relatively low risk of complications. However, after this initial period, surgeons in a geographically isolated region are likely to perform PAO infrequently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proper acetabular reorientation can improve long-term survivorship and decelerate the progression of degenerative changes [1]. Overcorrection can produce femoroacetabular impingement, undercorrection may leave a patient with persistent symptoms, and poor congruency of the joint can cause abnormal contact stresses and accelerated chondral damage [4,9]. Thorough preoperative planning is fundamental in PAO, and is based on plain radiographs and, more importantly, on CT imaging [6].…”
mentioning
confidence: 99%